Winthrop Rockefeller : from New Yorker to Arkansawyer, 1912-1956 - Kirk, John A., 1970- (The University of Arkansas Press, 2022)
"Why did Winthrop Rockefeller, the scion of one of the most powerful families in American history, move to a mountaintop in Arkansas from New York in the 1950s? In this richly researched biography of the former Arkansas governor, John A. Kirk delves into the historical record to fully unravel that mystery"--